Kinerja Mesin Air-Water Harvetser dengan Dua Koil Evaporator - Mirmanto, Mirmanto; Syahrul, Syahrul; Sutrisno, Ahsani (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2025)
In the dry season, certain areas have difficulty obtaining water for cooking or drinking. Therefore, it is necessary to present an air water harvester (AWH) machine to harvest water from the air. However, this machine is still limited in production. Various forms of evaporators have been applied to increase the productivity of water, but the machine has not yet produced sufficient water. This study examined the performance of AWH machines with two coil-shape evaporator. The performance mentioned here were the mass of water produced and the heat transfer rate from the air to the evaporator walls. In the open literature, no study like this has been found. This 2-coil evaporator in this study were tested with variations in incoming air velocity of 4 m/s, 5 m/s and 6 m/s with natural environmental conditions. The machine power used was 1 PK or 746 W. The results of this study show that the maximum water mass produced was 1.46 kg and the heat transfer rate was 360 W obtained the inlet air velocity of 5 m/s. So the increase in speed does not necessarily increase the mass of water and the heat transfer rate occurs.